Chemical Pulps for Writing and Printing Papers from Eucalrptus camaldulensis - Guha, S. R. D.; Kumar, Krishan (Indian Forester, 1968)
Laboratory experiments on the production of chemical pulps from Eucalyptus camaldulensis for production of writing and printing papers by sulphate process are described. The average fibre length of the pulp was 0.66 mm and the average fibre diameter was 0.011 mm. Easy bleaching pulps could be prepared under suitable conditions of digestion. The strength properties were, however, poorer than most other hardwoods tested in this laboratory.